Constructing a competitive order : the hidden history of British antitrust policies - Mercer, H. (Helen) (Cambridge University Press, 1995)
This book was first published in 1995. Businessmen have always had a strong inclination to avoid competition and regulate the market. Helen Mercer traces the evolution of British competition legislation designed to discourage such practices, from 1900 to 1964. Economic and legal textbooks attribute the dynamic behind the development of this legislation to an undefined 'public opinion' or to economists. Helen Mercer disagrees. She contends that competition policies have been shaped by the strategies of powerful business interests - at home and in the United States. Trade unions and organisations of labour have provided a consistent pressure on governments to legislate on private monopoly, in the face of sweeping criticisms of free enterprise. This book makes extensive use of archival sources to give a detailed analysis of government-industry relations. In the course of this it sheds new light on Britain's changing industrial structure, and offers pointers to the likely outcome of business regulation in Britain in the future.